الأصول العقدية المشتركة بين الأديان السما وية الثلاثة التوحيد أنموذجاً دراسة موضوعية- - العايب, أميرة; نوي, خولة; مولاتي, وفاء (جامعة الوادي university of eloued, 2019)
تناولت هذه الدراسة تسليط الضوء ع: موضو "الأ صول كالعقدية المشتر ة نبي الأديان السماوية الثلاثة ،التلحيد أنملذج ا " ، حيث كان الإشكال الذي نسعى إلى الإجابة عنه هو: في ماذا تشترك اليهودية والمسيحية مع الإسلام؟ وهل عقيدة التوحيد من ضمن هذه العقائد المشتركة؟ ولقد أجاب هذا البحث على ذلك من خلال ث لاثة مباحث مع مقدمة وخاتمة وكذا فهارس عامة. فالمبحث الأول كان بمثابة مدخل مفاهي مي فيه تعريف بمصطلحات الموضوع، أما المبحث الثاني ف مت كان علقاً بالحديث حول العقائد المشتركة بين الأديان السماوية الثلاثة، بينما المبحث الثالث فقد تمحور ة. الكلام فيه عن التوحيد في الأديان السماوي كما تضمنت الخاتمة أهم النتائج التي توصلنا إليها من خلال دراسة هذا المو عضو ، وكان أهمها أن التوحيد هو الأصل في الأديان السماوية الثلاثة، ولقد ورد في كتبهم المقدسة جميعاً على نصوص صريحة تدعو إليه.This attempts to highlight the topic: the origins and the main belief of the common creeds between the three religions and taking the Monotheism as an sample in this research. In this case: the issue or the problem that we are looking to find answer for it is: what are the common areas or points between Jewish and Christianity with Islam? In addition, does the Doctrine of Monotheism is included among these common creeds? This research has answered the two previous mentioned questions through three chapters with an introduction, a conclusion and an index. The first chapter is an introduction that deals with definitions of key terms in this topic. Further, the second chapter discussed the common creeds between the three religions whereas the third chapter dealt with the Monotheism in religions. Finally, the conclusion stated the main obtained results in conducting this study which is Monotheism as the origin and the main common belief in the three religions. At the end, all of that was mentioned and referred in all of their three Holy books also clear statements invites and call for Monotheism.
ليسانس